Using arbitration as a method for disputes resolution in Malaysia’s construction industry - Firas, Fadzil (2010)
Disputes in construction industry are a common thing and sometimes could not be avoided.Disputes majorly arise from misinterpretation or conflicts of engineering documents at any time during the execution of a contract.There are many methods/techniques used in resolving disputes.One of the popular recommendations is arbitration.This aim of this study is to study the process and procedures of arbitration as a method for disputes resolution, to identify and also analyze the causes of disputes and its solution techniques in construction industry.The questionnaires will be distributed by hand to all types of contractors limited to area in Kuala Lumpur and Kuantan. The data from the questionnaire survey will be analyzed in percentage and value of index by using frequency analysis and average index analysis.This study will show that many factors can contribute to disputes and its solution techniques.From the study,it is found that the cause of failure of planning and executing project is the main factor in construction dispute.Furthermore,negotiation is the best solution technique in construction dispute.In conclusion, determining the factors that contribute to disputes is important in order to recognize what is the suitable technique to resolve it as it is necessary for contractors that involved in Malaysian construction industry.Moreover,it is hoped that these findings can be used to overcome disputes that cause all the problems in Malaysian construction industry and hopefully will give new point of view on arbitration as a resolution technique to the contractors and construction industry in Malaysia.